Correlation of Iatrogenic mild hyperkalaemia and bradyarrhythmia: a problem of polypharmacy in elderly - Ahmad NH,; Tan, Toh Leong (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Mild hyperkalaemia does not typically cause cardiac symptoms. However, for an elderly patient on atrio-ventricular (AV) nodal blocker, even mild hyperkalaemia may result in disastrous outcome. We report a case of persistent bradyarrythmia caused by iatrogenic hyperkalaemia in a patient who had concomitant use of AV nodal medication. An 81-year-old lady with multiple comorbidities and a long list of medications presented with symptomatic bradyarrhythmia. She, in fact, had two AV nodal blockers in her prescription, a beta-blocker and amiodarone. Her potassium level was found to be mildly elevated due to acute renal failure. She remained bradycardic despite initial treatment and was subsequently dependant on intravenous isoproterenol until her renal function improved. This case highlights the different threshold for manifestation of hyperkalaemic symptoms in a growing group of patients: elderly patients with multiple comorbidities and polypharmacy.